Prevalence of Celiac Disease and Celiac Autoimmunity in the Toba Native Amerindian Community of Argentina. Issue 8 (2015) - Vázquez, Horacio; de la Paz Temprano, María; Sugai, Emilia; Scacchi, Stella M; Souza, Cecilia; Cisterna, Daniel; Smecuol, Edgardo; Moreno, María Laura; Longarini, Gabriela; Mazure, Roberto; Bartellini, María A; Verdú, Elena F; et al.
Abstract : BACKGROUND: Celiac disease (CD) is mostly recognized among subjects with a Caucasian ethnic ancestry. No studies have explored conditions predisposing Amerindians to CD. OBJECTIVE: To prospectively assess environmental, genetic and serological conditions associated with CD among members of the Toba native population attending a multidisciplinary sanitary mission. METHODS: An expert nutritionist determined daily gluten intake using an established questionnaire. Gene typing for the human leukocyte antigen (HLA) class II alleles was performed on DNA extracted from peripheral blood (HLA DQ2/DQ8 haplotype). Serum antibodies were immunoglobulin (Ig) A tissue transglutaminase (tTG) and the composite deamidated gliadin peptides/tTG Screen test. Positive cases were tested for IgA endomysial antibodies. RESULTS: A total of 144 subjects (55% female) were screened. The estimated mean gluten consumption was 43 g/day (range 3 g/day to 185 g/day). Genetic typing showed that 73 of 144 (50.7%) subjects had alleles associated with CD; 69 (94.5%) of these subjects had alleles for HLA DQ8 and four had DQ2 (5.5%). Four and six subjects had antibody concentrations above the cut-off established by the authors' laboratory (>3 times the upper limit of normal) for IgA tTG and deamidated gliadin peptides/tTG screen, respectively. Four of these had concomitant positivity for both assays and endomysial antibodies were positive in three subjects who also presented a predisposing haplotype. CONCLUSION: The present study was the first to detect CD in Amerindians. The native Toba ethnic population has very high daily gluten consumption and a predisposing genetic background. We detected subjects with persistent CD autoimmunity and, at least, three of them fulfilled serological criteria for CD diagnosis.